(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This research is motivated by the issuance of Presidential Regulation of the Republic of Indonesia No. 60 of 2013 concerning Integrative Holistic Early Childhood Development. And there are many PAUD institutions in our country, but the implementation of Integrative Holistic PAUD in Indonesia is still low, even reaching only a small part of the community. Various existing programs, namely the Toddler Family Development Program and the Posyandu that have been implemented so far, have not yet provided complete services, have no synergy and have not been integrated with aspects of education, health, and nutrition. Whereas the services provided should complement each other and be able to meet the basic needs of children, so that the level of development of children experiences optimal growth and development. The purpose of this research is to find out how the perception about the implementation of holistic integrated PAUD in Gorontalo Province is. And to obtain answers to these problems, researchers used qualitative methods, data collection techniques in the form of observation, documentation, and interview techniques. The results of the Perceptions about the Implementation of Integrative Holistic PAUD in Gorontalo Province, can be viewed from: 1). Implementation of Integrative Holistic PAUD, which has several indicators namely the implementation of education, health, nutrition, care, care, protection, and welfare, from all these indicators it can be concluded that the Implementation of Integrative Holistic PAUD in Gorontalo Province is not optimal. 2). The Role of Related Agencies, which has several indicators, namely carrying out counseling, technical guidance, supervision, evaluation, reporting, and from all these indicators it can be concluded that the Role of Related Agencies in the implementation of Holistic Integrative PAUD in Gorontalo Province is not optimal.